Specifics of Agricultural Risks Insurance System in the Republic of Kazakhstan - KHAN, Yury; NIKITINA, Galina; GRIGORUK, Vladimir; AKIMBEKOVA, Galya (Journal of Environmental Management and Tourism, 2017)
This article provides the analysis of influence of agricultural risk management on the economic development of the agricultural economies in developing countries on the example of Kazakhstan. The publication reflects the problems of the insurance development based on the generalization and application of foreign experience. Thus, the paper describes agricultural risk management system in Kazakhstan using integrated approach, which assumes cooperation between risk sources, farmers’ strategy and policy; comprehensive solutions for risk management in agriculture are offered. In this research, price variation in accordance with public-private partnership in agriculture of the country is examined. Statistical results of the empirical survey will help governments in developing countries to define agricultural risk management strategies that can be used as powerful tools for economic development of agriculture.